The Successful Queen without Glorification in the GOLDEN AGE Movie - Sofiani, Yulia; Sondari, Endang; Narawaty, Dede (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
Both England’s history and works are very interesting to be researched. In analyzing The Golden Age film, the hidden meaning is the purpose of this present research. The linguistic elements in the dialogue are primarily the data to analyze this film. Descriptive qualitative research is the methodology in this research. In the present research, reading, noting the important sentences and interpreting are the techniques for analyzing the Golden Age film dialogue. Critical discourse analysis is a tool to discover the hidden meaning of construction. As a result, through the use of linguistic elements, critical discourse analysis will be able to explain the hidden meaning, taken from the dialogue in The Golden Age movie.